2018
DOI: 10.5041/rmmj.10337
|View full text |Cite
|
Sign up to set email alerts
|

Specific Amino Acids Affect Cardiovascular Diseases and Atherogenesis via Protection against Macrophage Foam Cell Formation: Review Article

Abstract: The strong relationship between cardiovascular diseases (CVD), atherosclerosis, and endogenous or exogenous lipids has been recognized for decades, underestimating the contribution of other dietary components, such as amino acids, to the initiation of the underlying inflammatory disease. Recently, specific amino acids have been associated with incident cardiovascular disorders, suggesting their significant role in the pathogenesis of CVD. Special attention has been paid to the group of branched-chain amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 75 publications
4
48
0
Order By: Relevance
“…The connection between atherosclerosis and cholesterol accumulation is therefore, well-established (36). However, several recent studies indicate that the relative presence and/or absence of certain AAs may also contribute to atherosclerosis development and occurrence (37). One such study utilizing a rabbit atherosclerosis model reports alterations in the levels of several proteins, metabolites, and AAs in rabbit aorta, as well as in both rabbit and human plasma, suggesting that some of these molecules may be potential atherosclerosis biomarkers (38).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The connection between atherosclerosis and cholesterol accumulation is therefore, well-established (36). However, several recent studies indicate that the relative presence and/or absence of certain AAs may also contribute to atherosclerosis development and occurrence (37). One such study utilizing a rabbit atherosclerosis model reports alterations in the levels of several proteins, metabolites, and AAs in rabbit aorta, as well as in both rabbit and human plasma, suggesting that some of these molecules may be potential atherosclerosis biomarkers (38).…”
Section: Introductionmentioning
confidence: 99%
“…One such study utilizing a rabbit atherosclerosis model reports alterations in the levels of several proteins, metabolites, and AAs in rabbit aorta, as well as in both rabbit and human plasma, suggesting that some of these molecules may be potential atherosclerosis biomarkers (38). Some specific AAs such as Gly and BCAAs such as valine (Val), Leu, and isoleucine (Ile) can ameliorate cell metabolic processes through mitochondrial biogenesis (39), influencing macrophage foam cells and altering lipid metabolism (37). The effect of the described amino acids on atherosclerosis and related diseases in animal models and humans is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced HDL-cholesterol levels are associated with incidence of heart diseases ( 64 ) and our findings reflected that increased BCAA levels in the AA are correlated with marked reduction in HDL in our patient cohort. Prior reports have shown that levels of plasma dimethyl glycine and glycine improves risk prediction in patients with coronary heart disease and MI ( 45 , 65 ) and increased plasma glycine levels are protective against the risk of developing CVD ( 45 , 66 ). Our findings suggest that increases in BCAA catabolic enzyme expression in the AA alters plasma glycine profile making the heart more susceptible to cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid exists in two stereoisomeric forms, L forms and D forms, most of which are L-isomers. The amounts of D-AAs are dramatically low in human body [1]. So far, there are about 500 α-amino acids were discovered in nature.…”
Section: Introductionmentioning
confidence: 99%